Serum Levels of Antioxidant Minerals in Relation to Severity of HIV Infection Among Patients Attending Specialist Hospital Sokoto, Nigeria - Wasagu, I. Z.; Bunza, F. U. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2017)
Human immunodeficiency virus (HIV) positive patients are under chronic stress due to excessive production of reactive oxygen species (ROS). Micronutrients (including antioxidant minerals) deficiencies are common in HIV-related infections which may progress to acquired immunodeficiency syndrome (AIDS). The present study assessed the serum levels of antioxidant minerals in HIV-positive Highly Active Antiretroviral Therapy-naïve (HAART-naïve) patients. The study involved 128 subjects that comprised 96 HIV-positive HAART- naive patients and 32 age- and gender-matched HIV-negative controls. Levels of CD4 + count were enumerated using Flow Cytometry while serum levels of antioxidant minerals (Cu, Zn, and Fe) were estimated using Atomic Absorption Spectrophotometer (AAS) in controls (group1) and patients with CD4 + count of  ≥500 cells/µl (group 2), 200-499 cells/µl (group 3) and < 200 cells/µl (group 4). Results indicated that the HIV-positive HAART-naïve patients have significantly (p